A Symbolic Interaction in The Teaching of Gambang Semarang Music at School (Jurnal Seni Musik, 2023)
This study aims to provide a comprehensive description of the forms of symbolic interaction in the learning process of Semarang Gambang Music. The concept and theory of Symbolic Interaction belonging to George Herbert Mead (1934, 1938) which views the way of thinking about the mind (mind), self (self) and society (society) is used to examine the implementation of the learning process of Gambang Semarang Music. By using a qualitative approach, the data were obtained through the use of literature study techniques, observations, interviews, and document studies. Then some of the data that has been obtained is analyzed using steps according to Miles and Huberman's theory, namely analyzing data in three steps: 1) Data condensation, presenting data (data display), and drawing conclusions or verification (conclusion drawing and verification) ). Data condensation refers to the process of selecting, focusing, simplifying, abstracting, and transforming data. The results of the study show that symbolic interaction in learning Gambang Semarang Music occurs during the learning process. The forms of symbolic interaction between the teacher and the students are first, the teacher gives a signal (one, two, three, four) when leading the students to play the Semarang gambang musical instruments and sing songs together, and secondly, the teacher guides and guides them. students in reading sheet music notation prepared in the learning process